A review study of Bisphenol A - Danielsson, Emma (2020)
Bisphenol A (BPA) is one of the worlds most produced chemicals. This compound is widely employed as an additive in polymers such as polycarbonates and epoxy resins in the manufacturing of plastics to provide transparency, rigidity and resistance to the resins. Because of the suitable properties of these polymers, they are commonly utilized in materials having contact with foods, so called Food Contact Materials (FCMs). Studies in which these materials have been exposed to different kinds of stress, such as heat and long time of exposure, reveal that plastic monomers and additives such as BPA, tend to migrate from the plastic package to the food. This theory, combined with the fact that BPA has been reported as an Endocrine Disrupting Chemical (EDC) with affinity for estrogen receptors (ER), has given rise to the debate regarding the potential adverse health effects of BPA exposure in humans. The aim of this literature study was to examine the prevalence of BPA in FCMs manufactured from polycarbonates and epoxy resins and how this compound tends to migrate as a consequence of common use stress to these materials. Further, it also aimed to compile current research about the potential adverse health effects in humans as a result of exposure. Even though the researchers are divided, a lot of research suggests that high heat and long time of exposure have an impact on the migration of BPA from FCMs. Although, no measured concentrations have exceeded the tolerable daily intake (TDI) and the Specific Migration Limit (SML), which indicate that common use of plastic FCM not should constitute any health risks. Controversially, a lot of research has revealed adverse effects of BPA correlated to various important functions within the body, especially in pregnant women, fetal and young children. However, it should be considered that most documents that have been reviewed in this study are limited and that research on the long-term effects still is underinvestigated. Additionally, most studies have been performed on animals. To be able to draw any definitive conclusions regarding the possible detrimental effects of BPA in humans, more extensive research is needed.